The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1080/03069880902956983
|View full text |Cite
|
Sign up to set email alerts
|

Students’ psychological web consulting: function and outcome evaluation

Abstract: This paper refers to a brief interaction with a mental health professional via written electronic communication. Web consulting services have proved popular, but there is controversy regarding the efficacy of such brief interventions to address problems and enable service users to access other forms of counselling. University students are accustomed to new technologies and often present difficulties suitable for simple intervention. Additionally, interventions of this type lead to the creation of a 'database' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…This is perhaps related to a perceived benefit of the form, 'not having to talk face-to-face', that it allowed a level of distance and perceived anonymity that was seen as important. Anonymity and distance have been noted as benefits in online delivery (Efstathiou, 2009;Richards, 2009). It seemed pertinent for the eCBT group to be able to communicate with a professional and receive feedback while at the same time being at some distance and therefore providing some level of perceived anonymity.…”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps related to a perceived benefit of the form, 'not having to talk face-to-face', that it allowed a level of distance and perceived anonymity that was seen as important. Anonymity and distance have been noted as benefits in online delivery (Efstathiou, 2009;Richards, 2009). It seemed pertinent for the eCBT group to be able to communicate with a professional and receive feedback while at the same time being at some distance and therefore providing some level of perceived anonymity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the reader will know that the main research trial (Richards et al, in review) reported that the outcomes for both groups were equal at post-treatment and no significant differences were shown between the groups which suggests that there existed two routes to treatment success, one (cCBT) solely through non-relational CBT techniques and strategies and one (eCBT) that also benefited from a relational element (Richards et al, in review). Therefore, it would be interesting to investigate further whether a therapist-delivered non-CBT intervention based on exchanges of free text, such as those described by Richards (2009) andEfstathiou (2009), would equal outcomes from a self-administered cCBT program.…”
Section: Discussionmentioning
confidence: 99%
“…Online counseling has been provided as a standalone service and as an adjunct to other services (Efstathiou, 2009;Richards, 2009). Indeed, some computer-based self-administered treatments for a variety of disorders have included online counseling support, usually in the form of asynchronous post-sessions feedback, which appears to increase adherence and yield enhanced outcomes (Newman et al, 2011;Richards & Richardson, 2012).…”
Section: Online Counselingmentioning
confidence: 99%
“…: Barak & Bloch, 2006;Barak, Hen, Boniel-Nissim & Shapira, 2008;Cook & Doyle, 2002;Day & Schneider, 2002;Efstathiou, 2009;Hanley, 2009;Knaevelsrud & Maercker, 2006;Leibert, Archer, Munson & York, 2006;Richards, 2009). …”
Section: Online Counselingmentioning
confidence: 99%
See 1 more Smart Citation